2007
DOI: 10.1507/endocrj.k06-112
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, Folate and Cobalamin Levels in Hypothyroid Women before and after Treatment

Abstract: Abstract. Hypothyroidism may result in accelerated atherosclerosis. Hyperhomocysteinaemia is an independent risk factor for premature atherosclerotic vascular disease. The aim of the present study was to assess plasma total homocysteine (tHcy), folate and cobalamin concentrations in hypothyroid patients before and after treatment. Thirty-one hypothyroid and thirty health young women were studied. The hypothyroid patients were investigated in the untreated state and again after restoration of euthyroidism. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 36 publications
6
26
1
1
Order By: Relevance
“…L-T4 treatment significantly reduced the BMI, TC, HDL-C, LDL-C, TG, Hcy, and ApoB in our patients. In accordance with our results, Orzechowska-Pawilojc et al [27] also reported a significant decrease in the Hcy levels following L-T4 treatment in women with HO. Thyroid hormone replacement is a routine and conventional clinical practice for patients with HO and has been shown to ameliorate the lipid profiles in patients with atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…L-T4 treatment significantly reduced the BMI, TC, HDL-C, LDL-C, TG, Hcy, and ApoB in our patients. In accordance with our results, Orzechowska-Pawilojc et al [27] also reported a significant decrease in the Hcy levels following L-T4 treatment in women with HO. Thyroid hormone replacement is a routine and conventional clinical practice for patients with HO and has been shown to ameliorate the lipid profiles in patients with atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…In our observations, the subjects in the HO group had higher Hcy and LDL-C levels than the subjects in the SHO and control groups. Our results were consistent with the findings of previous studies, [2326] but were not in agreement with those reported by Orzechowska-Pawilojc et al, [27] who observed that the Hcy levels were nonsignificantly higher in patients with HO compared to healthy subjects. In HO patients, we found that the Hcy levels were positively correlated with the LDL-C level after adjustment for sex, BMI, FT4, and FBG.…”
Section: Discussionsupporting
confidence: 81%
“…Epidemiological studies of genetic polymorphism require large samples, especially for the evaluation of hyperhomocysteinemia as a risk factor for chronic complications (2,7,10). On the other hand, even when conducted on a reduced number of patients, clinical studies can point out changes in the metabolic pathways of homocysteine (4,28).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been pointed out as determinants of hyperhomocysteinemia, such as folate, vitamin B 6 and vitamin B 12 deficiencies (5), impaired renal function (6), hypothyroidism (7), as well as genetic predisposition. Hy perhomocysteinemia has been attributed to genetic defects of the remethylation pathway responsible for the conversion of homocysteine to methionine, or of the transsulfuration pathway, which converts homocysteine to cysteine.…”
Section: Introductionmentioning
confidence: 99%
“…An elevation of serum homocysteine levels in patients with overt hypothyroidism was reported (12.4 vs. 8.8 mmol/L in non-hypothyroid group, P 0.05) 42,43) . Thyroid hormone supplementation successfully reduced serum homocysteine levels 44,45) . In contrast, it was shown that subclinical hypothyroidism did not affect serum homocysteine level 44,46) .…”
Section: Direct Effects Of Thyroid Hormone On the Vasculaturementioning
confidence: 97%